Figuren des Messianischen in Schriften deutsch-jüdischer Intellektueller 1900-1933 - Dubbels, Elke (Conditio Judaica, 2011)
This study investigates the function of the recourse to the messianic tradition of Judaism among German-Jewish intellectuals between 1900 and 1933 (Benjamin, Bloch, Broch, Buber, Landauer, Rosenzweig, Scholem). Messianic figures of thought play an important role in the Jewish discourse of identity. Moreover, they are used productively in the creation of general theories in the realm of cultural studies (philosophy of language and history, theological-political thinking). The messianic figures of speech include not only figures of thought but also rhetorical figures of speech or tropes that reflect various constellations of sacrality and secularity in the modern era.